2007
DOI: 10.1002/hbm.20420
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional connectivity of primary visual cortex in early blindness

Abstract: In early blindness, the primary visual area (PVA) loses the ability to process visual information, and shifts to working on the processing of somatosensory input, auditory input, and some higherlevel cognitive functions. It has not yet been investigated whether such functional changes can lead to alterations of the functional connectivity between the PVA and other brain areas in resting state. The purpose of this study is to investigate the differences in the functional connectivity of the PVA between early bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
112
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(134 citation statements)
references
References 62 publications
17
112
2
Order By: Relevance
“…A finding that initially seems at odds with our data is that Liu et al (2007) and Yu et al (2008) reported decreased functional connectivity [i.e., correlations of the BOLD signal between brain regions (Friston et al, 1993)] in blind volunteers compared with controls between visual and auditory cortical areas during resting-state fMRI. However, if one considers that the visual cortex can also be activated by auditory stimuli in sighted if the task requires high levels of attention (Cate et al, 2009), the results seem more alike: possibly, the visual cortex of blind people is predominantly recruited during demanding tasks or when relevant information is supplied (Röder et al, 1996).…”
Section: Figurecontrasting
confidence: 96%
See 1 more Smart Citation
“…A finding that initially seems at odds with our data is that Liu et al (2007) and Yu et al (2008) reported decreased functional connectivity [i.e., correlations of the BOLD signal between brain regions (Friston et al, 1993)] in blind volunteers compared with controls between visual and auditory cortical areas during resting-state fMRI. However, if one considers that the visual cortex can also be activated by auditory stimuli in sighted if the task requires high levels of attention (Cate et al, 2009), the results seem more alike: possibly, the visual cortex of blind people is predominantly recruited during demanding tasks or when relevant information is supplied (Röder et al, 1996).…”
Section: Figurecontrasting
confidence: 96%
“…However, if one considers that the visual cortex can also be activated by auditory stimuli in sighted if the task requires high levels of attention (Cate et al, 2009), the results seem more alike: possibly, the visual cortex of blind people is predominantly recruited during demanding tasks or when relevant information is supplied (Röder et al, 1996). This would explain why resting-state studies (no attentional demands) failed to find coupling (Liu et al, 2007;Yu et al, 2008), whereas activation-based effective-connectivity studies did find enhanced coupling in the blind (Fujii et al, 2009;present study). This hypothesis is also backed by studies that found attentional modulations of visual cortex activity in the blind (Liotti et al, 1998;Stevens et al, 2007).…”
Section: Figurementioning
confidence: 99%
“…The thresholded map shows that a region within the pars opercularis and pars triangularis (classic Broca's area) has differential functional correlation to the left striate cortex in the blind and sighted, in general agreement with prior findings (Bedny et al, 2011;Watkins et al, 2012), although these prior studies used the lateral occipital cortex as a seed region. Also, in agreement with prior findings, a small area within the somatosensory cortex demonstrated decreased functional correlation to the left striate cortex in the blind population (Liu et al, 2007;Yu et al, 2008;Bedny et al, 2011).…”
Section: The Average Pattern Of Striate Correlation Is Similar In Thesupporting
confidence: 89%
“…We distinguish the modeling of fine-scale correlation within a cortical region from studies of the relationship between entire cortical regions (Liu et al, 2007;Yu et al, 2008;Watkins et al, 2012). By measuring the point-to-point structure of correlations within a cortical region, we may examine whether resting-state signals are related in a systematic way to the local functional organization of cortex.…”
Section: Discussionmentioning
confidence: 99%
“…ROI based connectivity analysis and whole brain connectivity are the two most common methods. Using these two methods, researchers can investigate alterations in patients with a brain disorder (He et al 2007b;Johnston et al 2008;Liu et al 2007Liu et al , 2008bSupekar et al 2008;Tian et al 2008;Wang et al 2006aWang et al , b, 2007Yu et al 2008;Zang et al 2007;Zhou et al 2008). In recent years, a functional network, the so-called "default mode network (DMN)" of the brain, a set of regions characterized by decreased neural activity during goal-oriented tasks (Raichle et al 2001), has attracted significant interest as well as controversy (Buckner and Vincent 2007;Morcom and Fletcher 2007a, b;Raichle and Snyder 2007).…”
Section: Functional Mrimentioning
confidence: 99%